The nature and dynamics of human rights violation in Bangladesh: an analysis - Quddus, S. M. Abdul; Hoque, Morshadul (IIUM Press, 2014)
Human rights are considered to be necessary for freedom, democratic governance and of course the maintenance of a reasonable quality of life in a particular state or society. However, Muslim states which are only several decades old showed generally a dismal performance in upholding and maintain human rights although being signatories to the United Nations Declaration of Human Rights. There is not a single country in the Muslim world in which peoples’ human rights or liberty, freedom, live in peace without fear and regular and competitive elections are ‘fully’ observed (Quddus, 2012). Bangladesh is not unique in these regard. In this chapter, we shall analyze the nature and dynamics human rights situation in Bangladesh in the current context and try to figure out the causes and consequences of human right violation in Bangladesh. Our point of departure is that human right violations of citizens constitute a significant problem in Bangladesh. Historically, all regimes showed dissatisfactory records of human right protection of weak section of the society and particularly political opponent of the regime. Human rights violation in Bangladesh by law enforcing agencies can be understood in different forms and partly as part of the regime’s strategies of controlling political rivals and or lack of interest to protect the rights of poor section of the society like women, children and the poor.